RESULTS OF RESEARCH ON SELECTION AND DEVELOPMENT OF TECHNOLOGY OF CULTIVATION OF VARIETIES OF BATATAS IN THE CONDITIONS OF SAMARKAND REGION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article presents the results of the study in the conditions of irrigated meadow-sierozem soils of the Zarafshan Valley during the cultivation of the selected varieties of sweet potatoes Khazina, Xar-Bay, Sochakinur, Japan, etc. with transparent film mulching, planting scheme 90x20x1 or 70x25x1 cm with a plant density of 55.5-57.1 thousand plants per hectare, irrigation regime during the growing season of plants according to pre-irrigation soil moisture 70-80% FMC (field moisture capacity), that is, with 12 irrigations according to scheme 5-7, application of mineral fertilizers at the rate of N200P160K100 kg/ha, the highest marketable (38.4- 56.4 t/ha) yield was ensured and the level of profitability 88.6-161.2%.